Prevalence and patterns of dietary supplement use and potential drug interactions among older adults in Saudi Arabia - Khawagi, Wael Y.; Alghamdi, Majd M.; Alfalqi, Laila M.; Alzahrani, Atheer A.; Alotaibi, Sara K.; Alsuwat, Joud J.; Baali, Fahad H.; Alruqayb, Wadia S.; Alfian, Sofa D.; Alshehri, Abdullah A. (Frontiers in Pharmacology, 2025)
IntroductionThe widespread use of dietary supplements (DSs) among older adults poses a potential risk for adverse interactions with prescribed medications, particularly in populations with multiple chronic conditions. In Saudi Arabia, where DSs commonly used, with limited data on the prevalence and risks of such interactions. This study aimed to assess the prevalence and patterns of DS use and evaluate potential drug–supplement interactions and their predictors among older adults.MethodsA cross-sectional study was conducted between November 2024 and March 2025 among outpatients aged ≥60 years. Data were collected through face-to-face interviews using a structured questionnaire. Drug–supplement interactions were assessed using Stockley’s Drug Interactions database. Data were analyzed using descriptive statistics, chi-square tests, and logistic regression in Stata.ResultsA total of 293 older adults participated in the study, of whom 245 (83.6%) reported using DSs, with vitamin D being the most commonly used (40.0%). Female gender (OR = 2.17; 95% CI: 1.16–4.07) and hypertension (OR = 2.35; 95% CI: 1.24–4.47) were significantly associated with DS use. Among the 232 participants who used both DS and prescribed medications, 40.1% had at least one potential drug–supplement interaction, while 10.3% experienced at least one supplement–supplement interaction. The most frequently implicated supplements were nicotinic acid, vitamin D, and omega-3 fatty acids. Diabetes (OR = 3.67; 95% CI: 2.06–6.54) and hypertension (OR = 2.34; 95% CI: 1.34–4.09) were significant predictors of potential interactions.ConclusionDS use is highly prevalent among older adults in Saudi Arabia, with a substantial proportion exposed to potential drug–supplement interactions. These findings highlight the importance of incorporating DS use assessment into routine clinical care for older adults and underscore the need for improved patient education and medication reconciliation practices to enhance medication safety.